Penegakan Hukum Ujaran Kebencian Yang Mengandung Diskriminasi Ras Dan Etnis Melalui Sosial Media - Muchammad Choirur Roziqin; Vieta Imelda Cornelis; Moh. Taufik (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Hate speech containing racial and ethnic discrimination on social media is increasingly becoming a serious problem in Indonesia. The existence of social media which can be accessed by almost all levels of society has a positive impact in terms of communication and information, but also increases the potential for the spread of hate speech which is detrimental to individuals and groups. This article aims to examine how law enforcement is against hate speech containing elements of racial and ethnic discrimination through social media in Indonesia. This research uses a qualitative approach, using literature study methods and in-depth interviews with legal practitioners, academics and information technology experts. The research results show that even though Indonesia has a legal basis regulating hate speech, its implementation still faces big challenges, especially related to monitoring in cyberspace and slow legal processes. This article also discusses the role of social media as a means of spreading discrimination and challenges to law enforcement, as well as providing recommendations for strengthening supervision and regulation regarding hate speech.